“Ardorosa maragata”: a atuação política de Ana Aurora do Amaral Lisboa em Rio Pardo - RS (1890-1920) - Finger, Eduardo (Universidade do Vale do Rio dos Sinos, 2020)
Ana Aurora do Amaral Lisboa (1860-1951) was a teacher, writer from Rio Grande do Sul and political activist. Born in Rio Pardo, Ana Aurora experienced important chapters of Brazilian history in the late 19th century and the first half of the 20th century. This research seeks to understand the political trajectory of this teacher and writer from Rio-Pardense, a notorious supporter of the Liberal Party and the Federalist Party of Rio Grande do Sul. We work with a diverse set of historical sources, such as (auto) biographical reports, correspondence, newspapers, criminal proceedings and inventory. Analyzing the socioeconomic profile of his family, it was possible to observe that the Amaral Lisboa were from a modest family. It is concluded that Ana Aurora's itinerary in the “world of letters”, as a teacher and writer, was leveraged by the social influence of her family. In the midst of the civil war of the Federalist Revolution (1893-1895), we understand an event that guided Ana Aurora's political life. In an action aimed at repairing individual and family honor, Ana Aurora gained notoriety in regional politics and, later, in historiography, for the skirmish with Antero Fontoura (political opponent), generating the opening of a criminal process and a series of media confrontations between both. Using writing as a resource, as a way to defend and participate in the civil conflict in the state, this biographical event was marked in memory about Ana Aurora and leveraged her career as a political columnist and "honorary member" of the federalists. Ana Aurora's performance in newspapers such as A Reforma and Gaspar Martins increased her reputation as an outstanding maragata, a performance marked by tension and strategies, being a woman who focused on political issues in mostly male public spaces.
Keywords: Ana Aurora do Amaral Lisboa; Rio Grande do Sul; Federalista; Trajetória política; Federalist; Political trajectory; ACCNPQ::Ciências Humanas::História